درجة تحقق معايير الجودة الشاملة في برامج إعداد المعلم في كلية التربية الأساسية في دولة الكويت من وجهة نظر الطلبة - العازمي، بدر حمد; الصديقى، هشام يوسف; المزيدي، حنان محمد (جامعة جنوب الوادي - كلية التربية بقنا, 2019)
هدفت الدراسة إلى معرفة درجة تحقق معايير الجودة الشاملة في برامج إعداد المعلم في كلية التربية الأساسية بدولة الكويت من وجهة نظر الطلاب. ولأجل ذلك تم إعداد أداة خاصة بالدراسة؛ وهي عبارة عن استبانة تكونت من (٤٦) عبارة؛ وزعت على (5) محاور تتعلق بمعايير الجودة الشاملة في أهداف البرنامج، سياسة القبول والتسجيل، طرق التدريس، أساليب ووسائل التقييم، والخدمات والتجهيزات. طبقت على عينة عشوائية تكونت من (443) طالبا وطالبة من طلبة كلية التربية الأساسية. وكشفت النتائج أن الأهداف الموضوعة وسياسات القبول والتسجيل وطرق التدريس وأساليب التقييم ووسائله تحقق معايير الجودة الشاملة بدرجة كبيرة، بينما تتحقق معايير الجودة في الخدمات والتجهيزات التي تيسير حاجات الطلبة بدرجة متوسطة. كما كشفت النتائج عدم وجود فروق ذات دلالة إحصائية بين متوسطات درجات أفراد العينة حول تقديرات لتوافر معايير الجودة الشاملة في برنامج الإعداد الأكاديمي بكلية التربية الأساسية تعزي لمتغيري الجنس والتخصص الدراسي، في حين وجدت فروق ذات دلالة إحصائية بين تقديرات أفراد العينة حول توافر معايير الجودة الشاملة المتصلة بالخدمات والتجهيزات اللازمة لبرنامج الأعداد الأكاديمي في كلية التربية الأساسية وفقا لمتغير الفرقة الدراسية لصالح طلبة الفرقة الثانية.
The study aimed to know the degree of achievement of the comprehensive quality standards in the teacher preparation programs in the College of Basic Education in Kuwait from the point of view of the students. To this end, a study tool was prepared. It consisted of 46 questionnaires distributed on 5 topics related to tire overall quality standards in the objectives of the program, admissions and registration policy, methods of teaching, evaluation methods and methods, services and equipment. Was applied to a random sample consisting of (443) male and female students of the Faculty of Basic Education. The results revealed that the objectives set, admissions policy, teaching methods, evaluation methods and means achieve the overall quality standards. while the quality standards in the services and equipments that facilitate the needs of the students are achieved to a medium degree. The results revealed that there were no statistically significant differences between the average scores of the sample members on the estimates of the availability of the total quality standards in the academic preparation program in the Faculty of Basic Education, in addition to the gender variables and the study specialization. With the necessary services and equipment for the academic preparation program at the Faculty of Basic Education According to the variable for the second year students.
Keywords: معايير الجودة الشاملة -- برامج إعداد المعلم -- كلية التربية الأساسية -- الكويت